Gene therapy for spinal muscular atrophy: the Qatari experience - Hossamaldein Gaber Ali (14152632) (2021)
Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disorder characterized by hypotonia, progressive muscle weakness, and wasting. Onasemnogene abeparvovec (Zolgensma®) is a novel gene therapy medicine, FDA-approved in May 2019 for the treatment of SMA. This study aimed to describe Qatari experience with onasemnogene abeparvovec by reviewing the clinical outcomes of 9 SMA children (7 SMA type 1 and 2 with SMA type 2) aged 4‒23 months treated between November 2019 and July 2020. Children <2 years with 5q SMA with a bi-allelic mutation in the SMN1 gene were eligible for gene therapy. Liver function (aspartate aminotransferase [AST], alanine aminotransferase [ALT], and total bilirubin), platelet count, coagulation profile, troponin-I levels, and motor scores (Children’s Hospital of Philadelphia Infant Test of Neuromuscular Disorders [CHOP INTEND]), were regularly monitored following gene therapy. All patients experienced elevated AST or ALT, two experienced high prothrombin time, and one experienced elevated bilirubin; all of these patients were asymptomatic. Furthermore, one event of vomiting after infusion was reported in one patient. Significant improvements in CHOP INTEND scores were observed following therapy. This study describes the short-term outcomes and safety of onasemnogene abeparvovec, which is well tolerated and shows promise for early efficacy. Other Information Published in: Gene Therapy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1038/s41434-021-00273-7 Additional institutions affiliated with: National Center for Rare Disease in Qatar - HMC